PELATIHAN ECOPRINT PADA TOTE BAG: SEBUAH IDE KREATIF DAN BERKELANJUTAN DI DESA LEBAK WANGI KECAMATAN WALANTAKA - Asnawi,; Ningsih, Ratu Septia; Alia, Salsabila Rahma; Ramdan, Dadan; Auliana, Sigit; Maulana Ns, Farhan; Ifvochy, Jammes (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
KKM UNIBA Group 1 Lebak Wangi Village conducted ecoprint training activities on tote bags in Lebak Wangi Village, Walantaka Sub-district, a creative and sustainable initiative that aims to empower local communities, especially women, in developing new skills in the field of handicrafts. Ecoprint is a natural dyeing technique that utilizes organic materials such as leaves, flowers and twigs to create unique motifs on fabric. The training was designed to introduce the eco-friendly ecoprint method, as well as provide an economic alternative for the villagers through the production of tote bags that can be sold as local products. The results of this training showed that the participants were able to master the basic ecoprint techniques and produce tote bag products that have aesthetic and commercial value. In addition, this activity also encourages awareness of the importance of protecting the environment through the use of natural materials and production processes that minimize waste. Thus, the ecoprint training in Lebak Wangi Village is not only a means of developing skills, but also plays a role in efforts to preserve the environment and improve the economic welfare of the local community.